The life experiences of Chinese women after late-life remarriage - Qiong Li; Jianyuan Huang; Jiayun Liu; Pei Zhao (BMC Women's Health)
Abstract Background Although late-life remarriage is not a rare phenomenon, it remains a controversial topic in China. Late-life remarriage involves many challenges and crises, especially for elderly women, who are often in weaker positions in remarriage relationships and face more difficulties. Currently, research on the life experiences of Chinese women after late-life remarriage is still limited. The purpose of this study is to explore and describe the life experiences of Chinese women who remarried later in life and to explore and describe their feelings about these experiences. Methods A phenomenological qualitative research design involving in-depth semistructured interviews was selected. Data analysis was performed via Colaizzi's methodology. Results Sixteen women participated in this study. Four themes and 8 subthemes emerged: (1) companionship and support attainment (daily companionship and economic support), (2) nanny-like treatment (undertaking most household chores and care work alone, suspected and guarded in terms of money), (3) degradation of social ties (decreased interaction with the original family, reduced contact with friends), and (4) concerns about the future (treatment costs after illness, housing issues after their new husband's death). Conclusion Our results reveal the complexity and vulnerability of the life experiences of Chinese women after late-life remarriage, which are the result of a combination of sociocultural and structural factors and reflect the pressure and injustice that women endure in a patriarchal society. Moreover, the study reveals the inadequacy of basic medical insurance and basic pension insurance systems. The results of this study will not only help society at large better understand the life experiences of Chinese women in stepfamilies after late-life remarriage but also help to provide numerous important recommendations for professionals who provide support to stepfamilies, as well as for policymakers.